2003
DOI: 10.1124/jpet.103.050013
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Angiogenesis by Endogenous Substance P Release and Neurokinin-1 Receptors During Neurogenic Inflammation

Abstract: Early angiogenesis is a key step in the transition from acute to persistent inflammation. The nervous system has long been known to play a role in inflammation, in part through the release of substance P from peripheral nerve terminals (neurogenic inflammation). Application of substance P can stimulate vessel growth in a variety of angiogenesis assays, although it was previously not known whether endogenous substance P released from sensory nerves could modulate angiogenesis. We hypothesized that endogenous su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 27 publications
4
65
1
3
Order By: Relevance
“…17,37 Furthermore, neoangiogenesis is a sequential process with early endothelial proliferation, followed by vessel neoformation and increased blood NK-1 receptor and aprepitant in melanomas M Muñ oz et al flow; the maturation of endogenous neurovascular regulatory systems occurs late in this process in inflamed tissues. 38,39 Vessel neoformation has also been associated with increased tissue innervation and expression of NK-1 receptors; 20 indeed, in a large majority of the tumors investigated, NK-1 receptors have been found on intratumoral and peritumoral blood vessels 19 and this finding is in agreement with the results reported herein. In addition, both SP and histamine (released from mast cells by the action of SP) are often concentrated in the connective tissue surrounding many tumors, including melanomas, and become so before the development of neoangiogenesis.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Alsupporting
confidence: 83%
“…17,37 Furthermore, neoangiogenesis is a sequential process with early endothelial proliferation, followed by vessel neoformation and increased blood NK-1 receptor and aprepitant in melanomas M Muñ oz et al flow; the maturation of endogenous neurovascular regulatory systems occurs late in this process in inflamed tissues. 38,39 Vessel neoformation has also been associated with increased tissue innervation and expression of NK-1 receptors; 20 indeed, in a large majority of the tumors investigated, NK-1 receptors have been found on intratumoral and peritumoral blood vessels 19 and this finding is in agreement with the results reported herein. In addition, both SP and histamine (released from mast cells by the action of SP) are often concentrated in the connective tissue surrounding many tumors, including melanomas, and become so before the development of neoangiogenesis.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Alsupporting
confidence: 83%
“…Notably, in contrast to antiangiogenic action of capsaicin in our system, capsaicin is reported recently to promote the neurogenic enhancement of angiogenesis in rat knee synovitis (43). Indeed, it was shown that intra-articular injection with high doses of capsaicin indirectly increases endothelial cell proliferation via release of endogenous substance P, an angiogenic neuropeptide, from sensory nerves.…”
Section: Discussionmentioning
confidence: 97%
“…In vivo experiments showed that endogenous substance P could be implicated in the neoangiogenesis connected with neurogenic inflammation (Seegers et al, 2003). Substance P and capsaicin, which induces substance P release from sensory nerve terminals, were injected in the rat knee and animals were sacrificed 24 h later.…”
Section: Substance Pmentioning
confidence: 99%